A Novel Method for Measuring Tension Generated in Stress Fibers by Applying External Forces - Sugita, Shukei (The Biophysical Society, 2011)
The distribution of contractile forces generated in cytoskeletal stress fibers (SFs) contributes to cellular dynamic functions such as migration and mechanotransduction. Here we describe a novel (to our knowledge) method for measuring local tensions in SFs based on the following procedure: 1), known forces of different magnitudes are applied to an SF in the direction perpendicular to its longitudinal axis; 2), force balance equations are used to calculate the resulting tensions in the SF from changes in the SF angle; and 3), the relationship between tension and applied force thus established is extrapolated to an applied force of zero to determine the preexisting tension in the SF. In this study, we measured tensions in SFs by attaching magnetic particles to them and applying known forces with an electromagnetic needle. Fluorescence microscopy was used to capture images of SFs fluorescently labeled with myosin II antibodies, and analysis of these images allowed the tension in the SFs to be measured. The average tension measured in this study was comparable to previous reports, which indicates that this method may become a powerful tool for elucidating the mechanisms by which cytoskeletal tensions affect cellular functions.